Autoestima y toma de decisiones en adolescentes, Huamachuco - 2013 - Catillo Barreto, Vilma Isela (2014)
The present research work of descriptive and correlational type, and transversal characteristic: it was applied in teenagers from the Educative Institution “Florencia de Mora de Sandoval”, district of Huamachuco in Sanchez Carrion province, during 2013 year with the purpose of determining the existing relation between the self-steem level and decision-making in Young people. The sample universe was a number of 130 students from both sexes. For recollecting data was used the instrument: Cooper-Smith’s self-esteem inventory and a decisionmaking test. The obtained information was processed and analyzed through of independence test of criteria (Chi-Squared Test x2), the results show that most of teenagers have a high level of self-esteem 51,5 per cent. In decision making, the 79, 2 per cent of them have an assertive decision. It was found a meaningful statistical relationship between the self-esteem and decision making variables